Facets of Mindfulness Mediate the Relationship between Depressive Symptoms and Smoking Behavior - Vinci, Christine (Mindfulness (N Y), 2016)
The relationship between cigarette smoking and depressive symptoms is well-established. Dispositional mindfulness has been associated with lower depressive symptoms, lower smoking dependence, and higher odds of smoking cessation. Given that mindfulness is multi-faceted, the current study examined which facets of mindfulness might mediate the relationship between depressive symptoms and smoking behavior. Participants (n = 72) completed the Smoking Consequences Questionnaire (SCQ), Center for Epidemiologic Studies Depression Scale (CESD), and Kentucky Inventory of Mindfulness Skills (KIMS; subscales-Observe, Describe, Acting with Awareness, Accepting without Judgment), and indicated number of cigarettes smoked per day (CPD). Simple mediation models (followed by multiple mediation when more than one facet was significant) tested whether mindfulness facets mediated the relationship between CESD and smoking behavior (CPD and SCQ subscales). Results indicated that 1) lower depressive symptoms were associated with higher Accepting without Judgment, which was related to lower Negative Reinforcement expectancies, 2) lower depressive symptoms were associated with increased Describe, which was associated with greater perceived Negative Consequences, 3) lower depressive symptoms were associated with higher Accepting without Judgment, which was associated with lower Negative Consequences expectancies, and 4) higher depressive symptoms were associated with higher scores on Observe, which related to both greater Positive Reinforcement and Negative Consequences expectancies. Greater Accepting without Judgment and Describe aspects of mindfulness may serve as protective factors in the relationship of depressive symptoms and smoking.